2016
DOI: 10.1039/c5sc04015a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer coordination promotes selective CO2reduction by cobalt phthalocyanine

Abstract: We present a study of the mechanistic factors that transform cobalt phthalocyanine from a catalyst that shows modest performance for the electrocatalytic reduction of CO2 to CO production into one of the most active and selective molecular catalyst reported in aqueous media when immobilized in a poly-4-vinylpyridine membrane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
219
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(235 citation statements)
references
References 92 publications
15
219
1
Order By: Relevance
“…The efficient molecule/CNT hybridization strategy allows us to realize one order of magnitude larger catalyst molecule loading (∼1.8 × 10 −8  mol cm −2 for CoPc or CoPc-CN) without compromising per-molecule activity, leading to one order of magnitude increase in catalytic current density compared with the previously reported CoPc-P4VP loaded on edge-plane graphite with similar TOF34. For hybrid materials with higher CoPc contents, lower TOFs were expectedly observed due to aggregation of molecules (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…The efficient molecule/CNT hybridization strategy allows us to realize one order of magnitude larger catalyst molecule loading (∼1.8 × 10 −8  mol cm −2 for CoPc or CoPc-CN) without compromising per-molecule activity, leading to one order of magnitude increase in catalytic current density compared with the previously reported CoPc-P4VP loaded on edge-plane graphite with similar TOF34. For hybrid materials with higher CoPc contents, lower TOFs were expectedly observed due to aggregation of molecules (Supplementary Table 2).…”
Section: Discussionmentioning
confidence: 92%
“…[16] Unfortunately,s uch an issue persists even at catalyst loadings below the theoretical monolayer coverage on carbonaceous substrates. [17][18][19][20][21] To improve the catalyst'sd ispersion, strengthening the interaction between the molecular catalysts and supports as ameans to overcome self-stacking is necessary. [17][18][19][20][21] To improve the catalyst'sd ispersion, strengthening the interaction between the molecular catalysts and supports as ameans to overcome self-stacking is necessary.…”
mentioning
confidence: 99%
“…[17][18][19][20][21] To improve the catalyst'sd ispersion, strengthening the interaction between the molecular catalysts and supports as ameans to overcome self-stacking is necessary. [19,22,23] Another approach is to directly graft molecular catalysts onto the conductive substrates via covalent bonding.Y ao et al covalently linked ac obalt porphyrin complex with peripheral acetylene groups to ad iamond surface decorated with alkyl azides by azidealkyne cycloaddition. [19,22,23] Another approach is to directly graft molecular catalysts onto the conductive substrates via covalent bonding.Y ao et al covalently linked ac obalt porphyrin complex with peripheral acetylene groups to ad iamond surface decorated with alkyl azides by azidealkyne cycloaddition.…”
mentioning
confidence: 99%
“…[11a] Based on the aforementioned considerations,w ed eveloped ah eterogeneous CO 2 RR electrocatalyst that is operative in aqueous solution by immobilizing planar Co II -2,3naphthalocyanine complexes (NapCo) on doped graphene based matrices and investigated the linkage effects.Graphene is as uitable substrate because it has high conductivity, stability under reductive environments and good reactivity to allow versatile linkages to connect with molecules. [17] We found that graphitic sulfoxide and carboxyl dopants of graphene served as major linking sites for NapCo through forming axial Co-O coordination. [17] We found that graphitic sulfoxide and carboxyl dopants of graphene served as major linking sites for NapCo through forming axial Co-O coordination.…”
Section: Introductionmentioning
confidence: 83%
“…XPS surveys showed that the Sd opants of SG-1/-2 both contained the oxidized sulfur structures (Figure 5b). [17] Although DFT calculation shows that the NapCo on graphitic SO and COO dopants afforded similar intrinsic activity,q uite different TOFs were observed experimentally on NapCo@SNG and NapCo@OG.Wetherefore investigated the redox responses of the immobilized Co sites by DPVs to verify if the electron communication between NapCo and the different doped graphenes was efficient. Thep rotonation of CO 2 to *COOH determines the overpotentials (Figure 5d).…”
Section: Insights Into Electrocatalysis Of Co Sites On S-doped Graphenementioning
confidence: 96%